2019
DOI: 10.1039/c8fo02408a
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin alleviates vascular alterations through modulation of Nrf-2/HO-1 and MMP pathways inl-NAME induced hypertensive rats

Abstract: Nobiletin alleviates l-NAME-induced vascular dysfunction and remodeling and superoxide production in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 63 publications
5
23
0
Order By: Relevance
“…In L-NAMEtreated rats, the BW, as well as the weight of testes and epididymides, did not differ from those in normal rats, as reported in a previous study (Adedara et al, 2018). It is well accepted that chronic treatment with L-NAME produces systemic vasoconstriction and high blood pressure because of decreased NO bioavailability (Potue et al, 2019). Testicular dysfunction induced by hypertension is associated with structural alterations, and reduced serum testosterone levels and StAR protein expression.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In L-NAMEtreated rats, the BW, as well as the weight of testes and epididymides, did not differ from those in normal rats, as reported in a previous study (Adedara et al, 2018). It is well accepted that chronic treatment with L-NAME produces systemic vasoconstriction and high blood pressure because of decreased NO bioavailability (Potue et al, 2019). Testicular dysfunction induced by hypertension is associated with structural alterations, and reduced serum testosterone levels and StAR protein expression.…”
Section: Discussionsupporting
confidence: 74%
“…The right testis was cut and homogenised with lysis buffer to extract proteins that were used to detect the protein expression of endothelial nitric oxide synthase (eNOS), Nrf2, HO-1 and StAR, as previously described (Chiangsaen et al, 2020;Potue et al, 2019). In each band, the protein intensities were observed and captured using an ImageQuant™400 imager (GE Healthcare).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Impairment of endothelium-dependent vasodilation in rats induced by L-NAME linked with reductions of eNOS protein expression and plasma nitrate/nitrite concentrations have been shown [ 5 ]. Moreover, aortic hypertrophy, including increases in vascular wall thickness, cross-sectional area, and wall-to-lumen ratio occurred after chronic L-NAME administration was shown [ 6 , 7 ]. Renin angiotensin system (RAS) activation characterized by increases in angiotensin converting enzyme activity and systemic angiotensin II (Ang II) concentration has also been observed in hypertensive rats with NO depletion [ 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the cerebral ischemia model, nobiletin protected by upregulating Nrf‐2, HO‐1 expressions . Potue et al indicated that nobiletin activates the Nrf‐2/HO‐1 pathway in hypertensive rats. According to our study, we observed that systemic administration of nobiletin in group 4 significantly increased the expression of Nrf‐2 and HO‐1 in the liver and kidney compared to the only APAP administered group, suggesting that activation of the Nrf‐2/ARE pathway and HO‐1 upregulation could be a potential hepatoprotective and nephroprotective mechanism.…”
Section: Discussionmentioning
confidence: 99%